ASSESSING THE EFFICIENCY AND SAFETY OF TRANEXAMIC ACID IN THE MANAGEMENT OF ACUTE GASTROINTESTINAL BLEEDING - Dr Shandana Altaf, Dr Mariana Amer, Dr Mohammad Tamhid, Muaaz Butt, Memoona Fareed, Dr. Muhammad Faisal Nadeem ,Kashif Lodhi, Ali Raza, Nael Abdulrahman Rashed Aljaddoa (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Acute gastrointestinal bleeding (GIB) positions very substantial clinical challenge owing to their possible for rapid deterioration and life-threatening complications. Tranexamic acid (TXA) has emerged as a potential therapeutic agent for managing GIB by its ability to promote clot stabilization and reduce bleeding. However, prior to its widespread use, rigorous assessment of its efficacy and safety is imperative.Aim: This study intended to evaluate efficiency and safety of tranexamic acid in management of acute gastrointestinal bleeding.Methods: A randomized controlled trial was conducted, involving individuals presenting through acute gastrointestinal bleeding. Participants were erratically allotted to receive either tranexamic acid or placebo in addition to standard care. The primary outcomes assessed were the rate of bleeding cessation, requirement for blood transfusion, and incidence of adverse events.Results: An overall of 120 participants were included in research, having 50 allotted to tranexamic acid group and 70 to placebo group. The administration of tranexamic acid resulted in a significantly higher rate of bleeding cessation compared to placebo (p < 0.05). Furthermore, tranexamic acid group exhibited a reduced need for blood transfusion and a comparable occurrence of adverse events associated to placebo group.Conclusion: The findings of the research indicate that tranexamic acid is efficacious in the management of acute gastrointestinal bleeding, demonstrating a higher rate of bleeding cessation and reduced need for blood transfusion without an enlarged danger of adverse events. These results support the incorporation of tranexamic acid into standard treatment protocols for acute gastrointestinal bleeding